Development of a novel loop mediated isothermal amplification assay (LAMP) for the rapid detection of epizootic haemorrhagic disease virus - Rajko-Nenow, P.; Howson, E.L.A.; Clark, D.; Hilton, N.; Ambagala, A.; Svitek, Nicholas; Flannery, J.; Batten, C. (MDPI, 2021)
Epizootic haemorragic disease (EHD) is an important disease of white-tailed deer and can cause a bluetongue-like illness in cattle. A definitive diagnosis of EHD relies on molecular assays such as real-time RT-qPCR or conventional PCR. Reverse transcription loop-mediated isothermal amplification (RT-LAMP) is a cost-effective, specific, and sensitive technique that provides an alternative to RT-qPCR. We designed two sets of specific primers targeting segment-9 of the EHD virus genome to enable the detection of western and eastern topotypes, and evaluated their performance in singleplex and multiplex formats using cell culture isolates (n = 43), field specimens (n = 20), and a proficiency panel (n = 10). The limit of detection of the eastern and western RT-LAMP assays was estimated as ~24.36 CT and as ~29.37 CT in relation to real-time RT-qPCR, respectively, indicating a greater sensitivity of the western topotype singleplex RT-LAMP. The sensitivity of the western topotype RT-LAMP assay, relative to the RT-qPCR assay, was 72.2%, indicating that it could be theoretically used to detect viraemic cervines and bovines. For the first time, an RT-LAMP assay was developed for the rapid detection of the EHD virus that could be used as either a field test or high throughput screening tool in established laboratories to control the spread of EHD.